PENGARUH EARNINGS PER SHARE (EPS), DEBT TO EQUITY RATIO (DER), CURRENT RATIO (CR) DAN PRICE TO BOOK VALUE (PBV) TERHADAP RETURN SAHAM BANK BUMN YANG TERDAFTAR DI BEI - Aulia, Edis Rama; Slamet, Nabillah Santi Dewi Lestari; Manda, Gusganda Suria (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study aims to test, analyze and empirically prove whether Earnings Per Share (EPS), Debt to Equity Ratio (DER), Current Ratio (CR) and Price to Book Value (PBV) have an effect on Stock Returns carried out on state-owned banking companies listed on the Indonesia Stock Exchange for the period 2018-2023. This research method was carried out using multiple linear regression analysis, with a quantitative research type and using a purposive sampling technique. The population in this study were banking companies listed on the Indonesia Stock Exchange for the period 2018-2023. With a sample of 4 state-owned banking companies listed on the Indonesia Stock Exchange for the period 2018-2023, and considerations based on predetermined criteria. The results of this study indicate that Debt to Equity Ratio (DER) and Price to Book Value (PBV) have a positive effect on Stock Returns. Meanwhile, Earnings Per Share (EPS) has a negative effect and Current Ratio (CR) is not significant on Stock Returns.